Evaluasi Program Bantuan Langsung Tunai Dana Desa Dalam Mengatasi Masalah Ekonomi Akibat Pandemi Covid-19 Di Desa Batujaya Kabupaten Karawang - Sopiatul Fazriah; Nanang Suparman; Sakrim Miharja (Ministrate: Jurnal Birokrasi dan Pemerintahan Daerah, 2022)
This study aims to evaluate the Village Fund Direct Cash Assistance (BLT) program in Batujaya Village. This research is a qualitative research. By using the program evaluation model according to Stufflebeam which consists of context evaluation, input evaluation, process evaluation, and product evaluation. Sources of data in this study came from primary data sources and secondary data sources with data collection techniques using observation, interviews, and documentation studies. The data analysis technique is done through data reduction, data presentation, and drawing conclusions. The result of the study that this program is indeed needed by the Batujaya Village community affected by the Covid-19. The implementation of the Village Fund Direct Cash Assistance program in Batujaya Village has also been carried out well. However, at the stage of collecting data on potential beneficiaries, there ware problems, namely it was difficult to determine which people really matched the established criteria, and the data in DTKS did not match the current conditions in the community. The limited village fund in the distribution of BLT Village Fund, which are only at least 40% of village fund, make this program not fully equitable. Regardless of that, this program is quite helpful in alleviating the needs of the affected village communities.therefore, there must be regular updating of DTKS data in order to minimize data that is not on target. Keywords: Policy, Policy Evaluation, Village Fund Direct Cash Assistance (BLT), Covid-19.